2001
DOI: 10.1152/ajpgi.2001.280.1.g43
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between flow rate and NO production in postnatal mesenteric arteries

Abstract: We studied mesenteric arterial arcades from 3- and 35-day-old swine to determine the relationship between perfusate flow rate and release of nitric oxide (NO) into mesenteric effluent. Mesenteric arterial arcades were perfused under controlled-flow conditions with a peristaltic pump using warm oxygenated Krebs buffer. Basal rates of NO production were 43.6 +/- 4.2 vs. 12.1 +/- 2.5 nmol/min in 3- vs. 35-day-old mesentery during perfusion at in vivo flow rates (9 vs. 20 ml/min, respectively). Rate of NO producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 22 publications
3
21
0
1
Order By: Relevance
“…Present data confirm these past observations and provide a mechanistic basis for the greater constitutive (1,19,23) and stimulated (24,30,31) production of NO within the newborn intestinal circulation, i.e., that expression of eNOS within the mesenteric artery increases after birth and remains elevated for at least the first 10 days of postnatal life. It is critical to note, however, that the present study is insufficient to allow Fig.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Present data confirm these past observations and provide a mechanistic basis for the greater constitutive (1,19,23) and stimulated (24,30,31) production of NO within the newborn intestinal circulation, i.e., that expression of eNOS within the mesenteric artery increases after birth and remains elevated for at least the first 10 days of postnatal life. It is critical to note, however, that the present study is insufficient to allow Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Generation of cGMP by in vitro mesenteric artery under basal or stimulated conditions is greater in rings from 3-than from 35-day-old subjects (23). Finally, the concentration of total nitrates (NO x ) is significantly greater within the effluent of buffer-perfused mesenteric arterial arcades from 3-than from 35-day-old piglets, and a direct relationship between the buffer flow rate, mesenteric arcade vascular resistance, and the concentration of NO x in the effluent is present only in younger subjects (30). This relationship is consistent with the observation that flow-mediated dilation, a process that can be NO-dependent (17), can be elicited in the intestinal circulation of 3-but not 35-day-old piglets (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that for some agonists, such as acetylcholine (29) and bradykinin (BK) (36), a rise in intracellular Ca 2ϩ is necessary for NO production. However, recent studies indicated that shear stress (9,30), isometric contraction (10), tyrosine phosphatase inhibitors (9,28,30), IGF-I (34), estrogen (5), and insulin (25) activate eNOS in isolated vessel preparations or in cultured cells in the absence of a change in [Ca 2ϩ ] i . These Ca 2ϩ -insensitive responses are blocked by tyrosine kinase inhibitors.…”
mentioning
confidence: 99%
“…A tissue slice was added to each well and the plate incubated at 37°C; thereafter, a second buffer sample was taken, the tissue slices were removed, blotted, and weighed. The NO concentration of conditioned buffer samples was determined by means of a Sievers NO Analyzer (Sievers Instruments, Boulder, CO) as previously reported (19). Paired observations were made for each perturbation and the average taken, and final data expressed as nM NO/L/g tissue.…”
Section: Methodsmentioning
confidence: 99%